Neo-rurality: roots of future in the field - Ferraresi, Giorgio (Scienze del Territorio, 2014)
Moving from the observation of a change taking place in the way of cultivating, defined as ‘new peasant agriculture’, and placing it in a relational milieu, lively and (inter) active, that tends to completely redefine the (social, institutional, economic, territorial, landscape and cultural) perception of rural world, this ‘vision’ interprets it as the first outline of a ‘return to earth’ path, where we can read plain signs of a possible reappearance of the historical role, authentically ‘primary’, of earth and agriculture. The effort to grasp what, in addition to the transience of parallel worlds, is generating this seed, today beginning to bear fruit, opens then a broad view (both in the diachronic and the synchronic sense) that tries to encompass the ‘long history’ of agriculture, its roots in time - past and present - and its projection towards a viable future.